GENETIC DETERMINANTS OF ACTIVATED FACTOR VII-ANTITHROMBIN COMPLEX (FVIIA-AT) PLASMA LEVELS AND MORTALITY IN PATIENTS WITH ANGIOGRAPHICALLY DEMONSTRATED CORONARY ARTERY DISEASE. (June 2022) - Pizzolo, Francesca; Veneri, Mariangela; Sartori, Filippo; Osti, Nicola; Donini, Martino; Moruzzi, Sara; Mazzi, Filippo; Castagna, Annalisa; Udali, Silvia; Pattini, Patrizia; Lunghi, Barbara; Baroni, Marcello; et al.
Abstract : Objective: Plasma concentration of activated factor VII (FVIIa)-antithrombin (AT) complex is considered as a marker of interaction between tissue factor (TF) and FVIIa. Data on possible genetic determinants of FVIIa-AT plasma levels are scarce until now. In this observational study we assessed 7 gene polymorphisms within 4 potential candidate genes, i.e. TF, coagulation factor 7 (F7), endothelial protein C receptor (EPCR), and LDL-receptor related protein 1 (LRP1) genes, which may contribute to the modulation of TF/FVIIa pathway. Design and method: Within the frame of Verona Heart Study and we selected 610 subjects (478 CAD and 132 CAD-free) for whom DNA for genotype analysis and FVIIa - ATplasma levels were available. Genotyping of TF (-603 A>G and + 5466 A>G), F7 (-402 G>A, -323 A1/A2 and R353Q), EPCR (219 A>G), and LRP1 (25 C>G) polymorphisms was performed on all the subjects. Patients with acute coronary syndromes and those taking anticoagulant drugs at enrolment were excluded. Results: TF -603 G>A, EPCR 219 A>G, and F7 -323 A1/A2 polymorphisms were predictors of FVIIa-AT plasma levels in adjusted linear regression models. Subjects carrying TF -603 A allele or EPCR 219 G allele had higher FVIIa-AT levels, while F7 A2 allele was associated with lower levels. Among the evaluated genotypes F7 -323 A1/A2 polymorphism was the strongest genetic determinant of FVIIa-AT variability and its association with FVIIa-AT levels was consistent with the influence on FVIIa levels. None of the polymorphisms had a different distribution between CAD and CAD-free subjects. In the follow-up analysis TF -603 G>A polymorphism was associated with mortality in CAD patients, with carriers of A allele having an increased risk of both total (sex and age-adjusted HR 1.93 with 95%CI 1.09–3.42) and cardiovascular mortality (sex and age-adjusted HR 2.54 with 95%CI 1.15–5.63), consistent with the higher FVIIa-AT levels. Conclusions: Polymorphisms in TF, EPCR, and F7 genes may contribute to the modulation of FVIIa-AT plasma levels. Results on the different genotypes suggest that the mechanisms originating the increase of FVIIa-AT plasma concentration may have a key role in CAD prognosis, addressing the interest on TF pathway.